Afraid to die - Jackson, Lisa. (New York : Kensington Pub., 2012)
Detectives Selena Alvarez and Regan Pescoli investigate after two women's bodies are found frozen and deliberately displayed with both victims wearing a piece of Selena's jewelry.
Keywords: Women detectives -- Oregon -- Fiction; Police -- Oregon -- Fiction; Women -- Crimes against -- Fiction; Serial murders -- Oregon -- Fiction; Murder -- Investigation -- Fiction; Suspense fiction; Mystery fiction